Parasitic risk factors in migrant horticultural families from Bolivia settled in the rural area of La Plata, Buenos Aires, Argentina - Falcone, Andrea Celina (2020)
Objective: The aims were to diagnose intestinal parasites in migrant horticultural families in the rural area of La Plata, and assess factors that increase the risk of parasitic infection. Materials and methods: Serial stool samples and anal swabs of 350 individuals were processed using sedimentation and flotation techniques. Socio-sanitary and environmental characteristics were surveyed using a semi-structured questionnaire. A generalized linear model was used to assess the change in parasitic prevalence with different predictor variables. Results: Of all examined individuals, 79.1% were parasitized, and 12 parasites were identified. Blastocystis sp. (58.9%), Entamoeba coli (26.3%), Enterobius vermicularis (26.0%), and Giardia lamblia (24.0%) were the most prevalent species. Risk factors were age group (<12 years), sampling site, and a basic education of parents. Conclusion: The high prevalence of intestinal parasites in horticultural families is associated with inadequate environmental sanitation, a limited access to education, and insufficient hygienic habits. An increase in parasitological references in integrated studies (human, animal and environmental health) would result in an understanding of the parasitic etiology, and the development of effective actions for the control of intestinal parasites.